2012
DOI: 10.1186/gm350
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of HLA associations with drug-induced liver injury: use of a HLA-genotyped DNA archive from healthy volunteers

Abstract: BackgroundDrug-induced liver injury (DILI) is one of the most common adverse reactions leading to product withdrawal post-marketing. Recently, genome-wide association studies have identified a number of human leukocyte antigen (HLA) alleles associated with DILI; however, the cellular and chemical mechanisms are not fully understood.MethodsTo study these mechanisms, we established an HLA-typed cell archive from 400 healthy volunteers. In addition, we utilized HLA genotype data from more than four million indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 40 publications
4
42
0
9
Order By: Relevance
“…6,[25][26][27][28] In contrast, flucloxacillin does not alter peptide binding to HLA-B*57:01, 28 which supports our hypothesis that functional flucloxacillin antigens derive from naturally processed drug-protein conjugates. Flucloxacillin-responsive CD8þ clones from patients with liver injury and HLA-B*57:01-positive volunteers were not stimulated with abacavir.…”
Section: Discussionsupporting
confidence: 73%
“…6,[25][26][27][28] In contrast, flucloxacillin does not alter peptide binding to HLA-B*57:01, 28 which supports our hypothesis that functional flucloxacillin antigens derive from naturally processed drug-protein conjugates. Flucloxacillin-responsive CD8þ clones from patients with liver injury and HLA-B*57:01-positive volunteers were not stimulated with abacavir.…”
Section: Discussionsupporting
confidence: 73%
“…(Imanishi et al, 1991c), Wales (Darke et al, 1998) and Northwest England (Alfirevic et al, 2012). Then, Tenerife Island population may seem to be related to both Mediterranean and Atlantic populations.…”
Section: Hla Allele Frequencies Found In Tenerife Population: Comparimentioning
confidence: 99%
“…To explore possible haplotype associations, we have recently used an in silico approach to analyze data stored in our database and in public repositories. We found that (1) different HLA alleles associated with druginduced liver injury are in strong linkage disequilibrium in populations of Caucasian and non-Caucasian ancestry, and (2) HLA risk alleles associated with unrelated drugs, such as flucloxacillin, ximelagatran, lapatinib, and antituberculosis drugs, reside on two main haplotypes (Alfirevic et al, 2012). Investigations are now clearly needed with lymphocytes from HLAtyped patients to investigate the immune mechanism (s) in different forms of HLA class II-associated IDRs.…”
Section: Hla Class Ii-associated Idrsmentioning
confidence: 99%